A REVIEW OF 3D PRINTING IN CONSTRUCTION AND ITS IMPACT ON THE LABOR MARKET - Hossain, Md. Aslam; Zhumabekova, Altynay; Paul, Suvash Chandra; Kim, Jong Ryeol (MDPI, 2020)
Construction industry is very labor-intensive and one of the major sources of employment in the world. The industry is experiencing low productivity with minimum technological innovations for decades. In recent times, various automation technologies including 3D printing have received increasing interests in construction. 3D printing in construction is found to be very promising to automate the construction processes and have the potential of saving laborious work, material waste, construction time, risky operation for humans, etc. There has been a comprehensive body of research conducted to understand the recent advances, future prospects and challenges of large-scale adoption of 3D printing in construction projects. Being one the labor-intensive industries, this study also investigates the possible impact on the labor market with increasing adoption of 3D printing in construction. It is found that 3D printing can reduce significant number of labors which can solve the labor shortage problem, especially for the countries where construction is heavily dependent on immigrant workers. In contrast, 3D printing might not be favorable for the countries where construction is one of the main workforces and labor is less expensive. Moreover, 3D construction printing will also require people with special skills related to this new technology.
Keywords: Type of access: Open Access; 3D construction printing; additive manufacturing; workforce; construction labor; immigrant workers